2021
DOI: 10.1177/10600280211049727
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gastrointestinal Bleeding on Treatment With Statin Alone or With Concomitant Administration of Warfarin: A Systematic Review and Meta-analysis of 5.3 Million Participants

Abstract: Objective: This study aimed to comprehensively evaluate the risk of gastrointestinal bleeding (GIB) with statin monotherapy or with concomitant warfarin use. Data Sources: PubMed, Web of Science, and EMBASE (via Scopus) were searched for observational studies that reported the risk of GIB in adults on statin therapy or with concomitant warfarin use until August 28, 2021. Study Selection and Data Extraction: Observational studies evaluating the risk of GIB in adults (age >18 years) on statin medication or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The use of antiplatelet drugs is a component of the HAS-BLED score, and aspirin combined with NOACs for the treatment of nonvalvular AF increases the risk of bleeding in patients who are susceptible to lifethreatening bleeding [25] . Although studies have found no association between statin use and increased risk of bleeding [26,27] , it was considered that atorvastatin calcium tablets may irritate the gastric mucosa, leading to side effects such as abdominal pain and bloating. After admission of our case, aspirin, amlodipine, and atorvastatin calcium tablets were discontinued to treat gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antiplatelet drugs is a component of the HAS-BLED score, and aspirin combined with NOACs for the treatment of nonvalvular AF increases the risk of bleeding in patients who are susceptible to lifethreatening bleeding [25] . Although studies have found no association between statin use and increased risk of bleeding [26,27] , it was considered that atorvastatin calcium tablets may irritate the gastric mucosa, leading to side effects such as abdominal pain and bloating. After admission of our case, aspirin, amlodipine, and atorvastatin calcium tablets were discontinued to treat gastrointestinal bleeding.…”
Section: Discussionmentioning
confidence: 99%